Benin : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) for Benin. The IMF staff has determined that Benin's PRSP contains a credible poverty reduction strategy. The main strengths of the PRSP are the comprehensiveness of the strategic framework and an effort to make explicit the linkages between policy actions and result indicators. However, the PRSP suffers from important shortcomings that the authorities will need to address during the first year of strategy implementation, so as to sharpen the poverty focus and make the strategy fully operational.